Factors associated with the perception of architectural barriers for access to health services in people with motor disabilities in Peru - Ramírez Moreno, Diana Carolina (2021)
Objectives: Determine the factors associated with the perception of architectural barriers in health services for people with motor disabilities. Methods and Materials: An analytical cross-sectional study was performed based on a secondary data base obtained from a specialized national disability survey (ENEDIS) in 2012. The participants were people older than 18 years who had motor disability. The architectural barriers considered were the absence of access ramps, security guardrails, adequate elevators, hygienic services for people with disabilities, places that provide information or information posters in health centers. For the analysis of our study, the complex nature of the sample was considered and prevalence rates with a 95% confidence interval were used. Chi-square and Student t tests were also used and, finally, an analysis of multiple regression variables was carried out. Poisson with robust variance where crude and adjusted PR were calculated. Results: The main results show that in 2012, people aged 65 years and older perceive access ramps and safety railings as barriers in an approximate 40% less probability compared to those who are 18 – 24 years old. In addition, people with a higher educational level (University, Masters and doctorate) perceive the access ramps and safety railings in health centers as barriers in an approximate 80% less probability compared to those who have no educational level. Finally, those who live in rural areas are associated with access ramps, safety railings, adequate elevators, and bathrooms for people with disabilities (p<0.001) Conclusions: In this study we have found that older people (mainly older adults) and with higher educational level perceive less arquitectural barriers in health care centers where they are treated. However, people living in rural areas are more likely to perceive architectural barriers compared to people in urban areas.